Species-Specific Exon Loss in Human Transcriptomes - Wang, Jinkai; Lu, Zhi-xiang; Tokheim, Collin J.; Miller, Sara E.; Xing, Yi (Molecular biology and evolution, 2015)
Changes in exon–intron structures and splicing patterns represent an important mechanism for the evolution of gene functions and species-specific regulatory networks. Although exon creation is widespread during primate and human evolution and has been studied extensively, much less is known about the scope and potential impact of human-specific exon loss events. Historically, transcriptome data and exon annotations are significantly biased toward humans over nonhuman primates. This ascertainment bias makes it challenging to discover human-specific exon loss events. We carried out a transcriptome-wide search of human-specific exon loss events, by taking advantage of RNA sequencing (RNA-seq) as a powerful and unbiased tool for exon discovery and annotation. Using RNA-seq data of humans, chimpanzees, and other primates, we reconstructed and compared transcript structures across the primate phylogeny. We discovered 33 candidate human-specific exon loss events, among which six exons passed stringent experimental filters for the complete loss of splicing activities in diverse human tissues. These events may result from human-specific deletion of genomic DNA, or small-scale sequence changes that inactivated splicing signals. The impact of human-specific exon loss events is predominantly regulatory. Three of the six events occurred in the 5′ untranslated region (5′-UTR) and affected cis-regulatory elements of mRNA translation. In SLC7A6, a gene encoding an amino acid transporter, luciferase reporter assays suggested that both a human-specific exon loss event and an independent human-specific single nucleotide substitution in the 5′-UTR increased mRNA translational efficiency. Our study provides novel insights into the molecular mechanisms and evolutionary consequences of exon loss during human evolution.